Enhancing Character Education and Islamic Values of Aswaja for IPNU IPPNU Students - Thohir, Muhyidin; Setiawan, Agus; Jannah, Asriatul; Alawiyah, Ika Trisnawati; Dea, Leli Fertiliana; Dewi, Yuli Ani Setyo (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
In recent years, the rise of concerning behaviors such as the dissemination of pornographic content, student demonstrations turning violent, inter-student conflicts, exam cheating, and drug involvement have highlighted a critical deficiency in student character and values. Character education rooted in the Islamic values ​​of Ahlussunah Waljama'ah (Aswaja) is essential to address these issues. This service aims to enhance and fortify the character and Aswaja values ​​among students, particularly those in the IPNU-IPPNU Metro City organization. Utilizing the Asset-Based Community Development (ABCD) approach, the program follows a structured path of discovery, dream, design, define, and destiny phases. The initiative has yielded significant outcomes, including heightened understanding and reinforcement of Aswaja values, practical application of these values ​​in students' daily lives, and active participation from parents and the community. These results underscore the program's effectiveness in fostering well-rounded, value-driven individuals.